Pengaruh Dosis Glifosat Dan Jarak Tanam Terhadap Pertumbuhan Gulma Dan Hasil Jagung (Zea Mays L. ) - Kharis - Triyono (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2010)
ABSTRACTField experiment was conducted to know the effect of glyphosate dose and plantspacing on the growth of weeds and to know the effect on the growth and yield of corn(zea mays L.).The factorial experiment conducted in Genengan Jumantono Karanganyar,used randomized completely block design (RCBD) consited of two factors, with threetimes replicated. The first factor was dose of glyphosate which consisted of four level :glyphosate 0 l/ha (G0), glyphosate 4 l/ha (G1), glyphosate 6 l/ha (G2), glyphosate 8 l/ha(G3). The second factor was plant spacing which consisted of three levels : 80 x 20 cm(J1), 80 x 30 cm (J2) , 80 x 40 cm (J3).Result of the experiment showed that application of gkphosate coused shifted inweeds composition, before sprayed Imperata cylindrica was dominated and aftersprayed did not dominate again. Plant spacing did not affect on the weeds and corngrowth, but affected on the yield of corn. Different dose of glyphosate did not affectsignificantly on the yield of corn, but by increasinjg dose of glyphosate was applied moredepressing on weeds, so the yield of corn more increasing.Key words : Glyphosate dose, plant spacing,yield of corn